2021
DOI: 10.1039/d0na00917b
|View full text |Cite
|
Sign up to set email alerts
|

Copper-fixed quat: a hybrid nanoparticle for application as a locally systemic pesticide (LSP) to manage bacterial spot disease of tomato

Abstract: A hybrid core–shell silica nanoparticle system integrating Cu nanoclusters and Quat combats resistance development of Xanthomonas perforans responsible for bacterial spot disease of tomatoes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Similar to reports by Ozcan et al, DDAC's surfactant properties may reduce the surface tension of spray droplets on the leaf surface and thus may improve wetting/coverage of the formulation. 19 Upon improved wetting, the localized accumulation of Zn and DDAC in droplets may have been minimized, thus mitigating some of the tissue damage observed as necrotic spots. Similar results were reported by Fu et al where the addition of organosilicon prevented the phytotoxicity typically observed after successive foliar treatments of 250 ppm zinc chloride solutions on 1 year old citrus seedlings.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to reports by Ozcan et al, DDAC's surfactant properties may reduce the surface tension of spray droplets on the leaf surface and thus may improve wetting/coverage of the formulation. 19 Upon improved wetting, the localized accumulation of Zn and DDAC in droplets may have been minimized, thus mitigating some of the tissue damage observed as necrotic spots. Similar results were reported by Fu et al where the addition of organosilicon prevented the phytotoxicity typically observed after successive foliar treatments of 250 ppm zinc chloride solutions on 1 year old citrus seedlings.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…19 The use of surfactants in agrochemical formulations is common to improve the efficacy of embodied pesticides. 11,13,16,19 When considering a homologues series of Quats, wetting is typically increased with the increasing size of alkyl groups. 14 Due to increased and more uniform coverage, wetting agents may promote the prolonged retention of actives on the target after foliar application under field conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…15 In addition to their application as nanocarriers for pesticide substances and plant nutrition, nanoparticles can act as vectors of genetic material to cells, overcoming the limitations of conventional transformation methods. 16 The nanomaterials can perform the delivery of different biomolecules such as DNA, miRNA, siRNA, ribonucleoproteins, etc. These systems are considered noncytotoxic vectors and present biocompatibility.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A variety of nanoplatforms, commonly studied for applications in the fields of materials, electronic devices, and medicine, have been attracting interest for applications in agriculture . In addition to their application as nanocarriers for pesticide substances and plant nutrition, nanoparticles can act as vectors of genetic material to cells, overcoming the limitations of conventional transformation methods . The nanomaterials can perform the delivery of different biomolecules such as DNA, miRNA, siRNA, ribonucleoproteins, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, nanotechnology could represent a great breakthrough in sustainable pesticide formulation [ 2 , 37 , 38 ]. Antimicrobial and resistance inductance properties of several nanoparticles synthetized from inorganic materials, such as zinc, copper, magnesium, silver, silica and graphene, were already positively assayed against tomato bacterial spot and speck diseases [ 39 , 40 , 41 , 42 , 43 ]. Furthermore, many materials can be engineered to obtain carriers at the nanoscale level, which can be functionalized with active principles.…”
Section: Introductionmentioning
confidence: 99%